Quasi-continuous time-stretched photon Doppler velocimetry - Lv, Linjie; Yang, Yongjun; Wu, Tengfei; Han, Jibo; Ma, Pengmou; Chen, Xiangmiao; Khan, Abdul Qayyum (Frontiers in Physics, 2022)
In transient high-speed scenes such as chemical explosions, magnetic compression, electric explosion, and laser-driven flyer, the target object can accelerate from 0 to tens of kilometers/s in a few nanoseconds. The bandwidth of the electrical digital-to-analog converter of the photon Doppler velocimetry system will reach several GHz, even tens of GHz. The time-stretched photon Doppler velocimetry relies on the time-stretched characteristics of the femtosecond laser to reduce the frequency of the Doppler shift signal of the target object in the optical domain, which breaks through the bandwidth limitations of photoelectric detectors and electrical digital to analog converters. A quasi-continuous time-stretched photon Doppler velocimetry is proposed in this paper. The velocity signal of the target object is encoded on multiple stretched chirp pulses, avoiding sampling interruptions and trigger condition limitations; in the signal demodulation, the error compensation algorithm is used to compensate for the frequency shift signal, which reduces the system error caused by the displacement and increases the effective recording time. This paper adopts the high-power nanosecond laser to drive the metal film to produce a high-speed target. The peak velocity of the flyer can reach 3.5km/s in nanoseconds. The 400km single-mode fiber is used as the dispersion medium of the femtosecond laser, forming a scale factor of 1/2. Finally, the system reduces the frequency difference signal from 4.4GHz to 2.2GHz, and the experimental error is less than 5% by comparing with the results of the conventional photon Doppler velocimeter This technology will be able to be applied to the velocity measurement of dynamic high-pressure technology loading flyers and provide a new measurement method for the field of transient high-speed dynamic process measurement.